Self Thromboplastin - Prothrombin Time. A New Test in Hemorrhagic Syndromes and in the Control of Anticoagulant Therapy - Berkarda, B; Derman, U (Thrombosis and Haemostasis, 1964)
1. A new method where the patients own plasma is clotted by the addition of his own whole blood hemolyzate is described. The hemolyzate here is the thromboplastinic source. The clotting time is recorded and called the Self Thromboplastin-Prothrombin time. This test gives abnormal results in cases with defective intrinsic prothrombin activation. The fact that it is abnormal in hypoproconvertinemia proves that it also reflects deficiencies in extrinsic activation of prothrombin.2. This test is applicable for screening of hemorrhagic diseases concerning the second, third and fourth stages of coagulation. It can be used in the control of anticoagulant therapy with dicoumarol derivatives and heparin by means of a dilution curve.